Governance, COVID-19 and Youth Uprising in Nigeria: From Peaceful to Violent Engagement - Okoli, Rowland Chukwuma; Iwuamadi, Kelechi Chijioke; Ugwuozor , Samuel (University of Nigeria Journal of Political Economy, 2021)
This study provided a historical account of youth uprising in Nigeria since the return to civil rule in 1999 and demonstrated how the COVID-19 pandemic impacted on the strategies of youth social movement in Nigeria. It does so within the context of the following questions: Why did the passage of age reduction bill fail to end violent youth movements across Nigeria? How did the COVID-19 pandemic deepen the adoption of violence as a strategy for youth led social movement? The study employed the process tracing technique (Collier, 2011) and relied on secondary sources for data collection. The study is anchored on the Frustration-Aggression theory to present two key arguments: The age reduction bill increased the space for youth political participation but did not translate to enhanced governance needed to address frustrations which drives youth uprising in the country. Secondly, the ineffective governance of COVID-19 palliatives and lockdown measures associated with the pandemic interacted with entrenched economic and political frustration of the youth to trigger adoption of violent engagement strategies by the youth as exemplified by the #EndSARS protest. The study contends that youth-led social movement in Nigeria has oscillated from peaceful to violent engagement in reaction to the character of governance at every epoch.